Surgical natural uveoscleral outflow activation in the primary and secondary glaucoma patients treatment - N. G. Zavgorodnaya; T. P. Gaidarzhi (Patologìâ)
Aims. In the article the technical aspects of a new uveoscleral outfl ow surgical activating way are presented. Methods and results. 86 patients (90 eyes) with primary and secondary glaucoma were treated. Early and remote results of the offered operation directed on the improvement of natural uveoscleral intraocular liquid outfl ow are resulted. Effi ciency of operation in the achievement of intraocular pressure proof indemnifi cation in patients with glaucoma is proved. Conclusion. Implementation of angular-uveal drainage with implantation of collagenous drain Xenoplast is recommended as an alternative operation at the different stages of glaucomatous process.